Strategic Curriculum Design for Brand Building: An Analysis of the Islamic Fashion Institute's Curriculum as a Strategic Communication Tool in Constructing Institutional Brand Identity and Brand Equity - Hanni Haerani; Dede L Chaerowati (International Journal Labs, 2026)
This research aims to analyze how a fashion design training curriculum based on Muslim dress principles serves as a strategic communication tool to build institutional brand identity and brand equity at the Islamic Fashion Institute (IFI), Bandung, Indonesia. The study employs a qualitative approach with an intrinsic case study method. Data were collected through triangulation, including in-depth interviews with curriculum designers and instructors, document analysis of the syllabi, and focus group discussions (FGD) with alumni and active students. Thematic analysis was applied using Kapferer’s Brand Identity Prism and Keller’s Customer-Based Brand Equity (CBBE) framework. The results indicate that the Sharia-based curriculum acts as the core brand message and a meaning-making system. The integration of Fiqh (Islamic Jurisprudence) of fashion, Islamic aesthetics, and Sharia business ethics serves as a potent brand differentiator. This